Saddu Dzari’ah: Islamic Marriage Guidance as a Prevention of Household Violence - Ainul Yaqin; Muhammad Is’Adur Rofiq (Risalah, Jurnal Pendidikan dan Studi Islam, 2023)
This study aims to determine whether premarital marriage guidance can be based on the Saddu Dzari’ah method. Descriptive research method used in this study. This study uses a literature review approach by collecting data sourced from books, news and articles and reputable journals. The results of this study in the form of divorce due to domestic violence (domestic violence) will have an impact on the psychological well-being of the wife, especially for the children. Because divorce is seen from the start as a form of action which, if done with consideration, both have the potential to cause discussions about what is permissible and what is not. Second, it can be seen from the impact of divorce which will break the relationship between the family of men and women. Third, judging from the degree of harm caused by the demonstration of separation, it brings specific losses because separation is a legitimate demonstration but is hated by Allah SWT. The Saddu Dzari’ah method can thus be used as the basis for a law implementing Marriage Guidance (BINWIN). The use of this strategy is essentially being careful in doing good while dealing with conflicts between maslahat and mafsadah. between reconciliation and divorce. Precautions must be taken because the chances of meeting the mafsadah are very high.